2015
DOI: 10.1002/anie.201411234
|View full text |Cite
|
Sign up to set email alerts
|

The Fluorenyl Cation

Abstract: The fluorenyl cation is a textbook example for a 4π antiaromatic cation. However, contrasting results have been published on how the annelated benzene rings compensate the destabilizing effect of the 4π antiaromatic five-membered ring in its core. Whereas previous attempts to synthesize this cation in superacidic media resulted in undefined polymeric material only, we herein report that it can be generated and isolated in amorphous water ice at temperatures below 30 K by photolysis of diazofluorene. Under thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
62
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 26 publications
9
62
0
Order By: Relevance
“…Ab road feature at 515 nm, which was observed after photolysis of 9-diazafluorene in amorphous water ice,w as previously assigned to the absorption of FL9 + , [7] and is close to the 518 nm band detected in the present studies.T he 518 nm system is the most intense absorption observed after deposition of C 13 H 9 + ions produced from fluorene,and hence FL9 + is proposed to be the carrier of the 518 nm system. However,t here are two other cationic origins at 538 and 392 nm, and for acomplete structural assignment, theoretical calculations on the plausible isomers of C 13 H 9 + were carried out.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…Ab road feature at 515 nm, which was observed after photolysis of 9-diazafluorene in amorphous water ice,w as previously assigned to the absorption of FL9 + , [7] and is close to the 518 nm band detected in the present studies.T he 518 nm system is the most intense absorption observed after deposition of C 13 H 9 + ions produced from fluorene,and hence FL9 + is proposed to be the carrier of the 518 nm system. However,t here are two other cationic origins at 538 and 392 nm, and for acomplete structural assignment, theoretical calculations on the plausible isomers of C 13 H 9 + were carried out.…”
supporting
confidence: 89%
“…[3] Recently,a ni nvestigation of the photochemical products of 9-DAFL in amorphous water ice in the infrared and optical domain confirmed that the broad absorption at 515 nm originates from FL9 + . [7] TheFL9 À anion was the focus of gas-phase photoelectron studies that provided vibrational frequencies for the ground state and the first excited state of neutral FL9. [8,9] This radical, which was produced by electron bombardment and UV photolysis of fluorene and trapped in solid argon, has also been studied by infrared, Raman, and UV/Vis spectroscopy.…”
mentioning
confidence: 99%
“…In ar ecent report aboutt he unsubstituted 9fluorenyl cation, Sander et al notedt he difficulties associated with generating and observing the unstablef luorenyl cation. [10] Our studies show that acid-promoted cyclizationso fb iaryl ketones (5)p rovide convenient access to these cationic species.…”
mentioning
confidence: 76%
“…Thus, the ground state of 1 is switched from triplet to singlet.T his is not only observed in cryogenic matrices at low temperature, [10,11] but also in solution at room temperature. [12] Carbene 2 shows as imilar behavior, [13] whereasi n3 the singlet-triplet splitting is too large to be overcome by hydrogen bonding.H alogen bondings tabilizes the singlet stateso fc arbenes even more than hydrogen bonding, [14] and BF 3 formss tronglys tabilizedd onor-acceptor complexes, [15,16] similart oN H 3 -BF 3 .T hese resultss tress the high basicity of the closed-shell singlet stateso fc arbenes.…”
Section: Introductionmentioning
confidence: 99%